Ocular parameters before and after steep Trendelenburg positioning for robotic-assisted laparoscopic radical prostatectomy - Mizumoto K; Gosho M; Iwaki M; Zako M (Clinical Ophthalmology, 2017)
Kyoichi Mizumoto,1 Masahiko Gosho,2 Masayoshi Iwaki,1 Masahiro Zako3 1Department of Ophthalmology, Aichi Medical University, Nagakute, Aichi, Japan; 2Department of Clinical Trial and Clinical Epidemiology, Faculty of Medicine, University of Tsukuba, Tsukuba, Ibaraki, Japan; 3Department of Ophthalmology, Asai Hospital, Seto, Aichi, Japan Purpose: Intraocular pressure (IOP) increases in patients in a steep Trendelenburg position during robotic-assisted laparoscopic radical prostatectomy (RALP). We hypothesized that a steep Trendelenburg position during RALP, an unusual systemic condition involving a transiently increased IOP, may induce ocular pathology that can be detected by detailed evaluations long after the surgery. This study aims to explore ocular structural and functional parameters in patients before and in the long term after the surgery. Patients and methods: A comparative observational study was performed. A total of 44 eyes of 22 male patients scheduled for RALP at Aichi Medical University from August 2012 to July 2013 were included. Clinical parameters before and after RALP were compared. Perioperative IOP was measured immediately post-induction of anesthesia in the flat supine position (T1), immediately post-steep Trendelenburg position (T2), and prior to returning to a flat supine position while in a steep Trendelenburg position (T3). The thicknesses of the peripapillary retinal nerve fiber layer, ganglion cell complex (GCC), and central fovea were measured with spectral domain optical coherence tomography. Humphrey perimetry was performed before and at 3 and 6 months after surgery. Results: The average IOPs (mmHg) at each stage were T1=10.4, T2=21.7, and T3=29.6, and differed significantly. The mean visual acuity (logarithm of the minimal angle of resolution), IOP, mean deviation, and pattern standard deviation measured by the Humphrey field analyzer showed no statistically significant difference before and after surgery. The ganglion cell complex and retinal nerve fiber layer thicknesses measured at each location and the central fovea thicknesses measured before and after surgery did not differ significantly. Conclusion: No significant disorders in ocular structural and functional parameters were found until long after RALP. Keywords: retinal nerve fiber layer, spectral domain optical coherence tomography, steep Trendelenburg position, Humphrey perimetry, robotic-assisted laparoscopic radical prostatectomy